Limiting the Principle of Banking Secrecy A Comparative study - Alaa Omar, Assist. Lect. Ban (Basra studies journal, 2024)
Limiting and restricting banking secrecy is important to facilitate the procedures for controlling and monitoring the sources of funds, and for controlling money launderers from exploiting the banking systems to facilitate their commission of money laundering and smuggling crimes. The research was divided into two sections through which the researcher presents some of the steps taken by international agreements and comparative legislation to limit banking secrecy. The most important result have reached is the absolute application of the commitment to banking secrecy raises many problems and suspicions regarding the legitimacy of the funds deposited in these banks, especially since the basic purpose of banking secrecy is to preserve the legitimate interests of customers and not to disclose private data. Therefore, the Iraqi legislator must intervene to stipulate the setting of some limits regulating banking secrecy.